Dose escalation and associated predictors of survival with consolidative thoracic radiotherapy in extensive stage small cell lung cancer (SCLC): A National Cancer Database (NCDB) propensity-matched analysis. (October 2018) - Hasan, Shaakir; Renz, Paul; Turrisi, Andrew; Colonias, Athanasios; Finley, Gene; Wegner, Rodney E.
Highlights: We used the NCDB to analyze consolidative thoracic radiation in extensive stage SCLC. A dose of at least 45 Gy compared to less than 45 Gy was an independent predictor of survival. In select extensive stage SCLC patients dose escalated thoracic radiotherapy may be considered. Abstract: Purpose: Randomized studies have demonstrated a survival benefit for consolidative thoracic radiotherapy (TRT) in extensive stage (ES) small cell lung cancer (SCLC), however the radiation dose and optimal selection criteria are often debated. Methods: We analyzed 3280 stage IV SCLC treated with double-agent chemotherapy and TRT within the National Cancer Data Base (NCDB) and evaluated the differences in selection patterns and survival outcomes for patients who received at least 45 Gy of TRT and those who received <45 Gy. Univariable and multivariable analyses identified characteristics predictive of overall survival. Propensity-adjusted Cox proportional hazard ratios for survival were used to account for indication bias between the two dose arms. Results: There were 1621 patients in the <45 Gy group (most common 30 Gy) and 1659 patients in the 45 Gy or higher group (most common 45 Gy). White patients, T1-T3 lesions, an absence of brain/liver/bone metastases, and starting TRT after 12 weeks of chemotherapy were associated with the higher dose group. With multivariable analysis, TRT to at least 45 Gy was an independent predictor of improved survival (HR = 0.78, P < 0.001) along with female gender, age <65, lower comorbidity score, starting TRT 12 weeks after chemotherapy, and the absence of brain/liver/bone metastases (P < 0.01). Propensity adjusted regression model showed a persistent correlation between a higher dose and survival (HR = 0.74, P < 0.001). Survival at 1 and 2 years for the 45 Gy or higher arm was 58.1% and 25.2% compared to 43.8% and 15.1% for the <45 Gy arm (P < 0.001). Conclusion: In the largest analysis of consolidative thoracic radiotherapy in ES-SCLC to date, dose escalation to at least 45 Gy was an independent predictor for increased survival. These findings may be validated in ongoing prospective studies.